A Prospective Study to Determine the Timing of Complete Fusion of Spheno-Occipital Synchondrosis Using Computed Tomography - Hariprasad T. Nambiar; Aysha Mehanaz; Nitika C. Panakkal; Suresh S; Visakh T (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The Spheno-occipital synchondrosis (SOS) has a significant role in role in the field of forensic,medical and anthropological sciences for age analysis. Therefore, SOS can help estimating age dependingon different stages of closure. Therefore, the present study aimed to evaluate the timing of complete fusionof Spheno-occipital synchondrosis using computed tomography.Methods: A prospective study including 110 subjects was conducted in which 55 males and 55 femalesbetween the ages of 15-25. All CT examinations were performed on a 128 slice incisive CT, Philips and16- slice big bore CT, Philips. The sagittal image was used for analysis the stage of spheno-occipital fusion.Based on the stage of fusion of SOS, patients were categorized into stage 0 indicating partial/no fusion andstage 1indicating complete closure of the SOS. An experienced radiologist scored all images.Conclusion: The mean age of male cases with complete SOS closure was 20.3 ± 3 years for males and20 ± 3.1 years for females. The study results show that by age of 20, no individual will belong to stage 0irrespective of gender and all individuals would have completely fused SOS.